ผลของการใช้บทเรียนคอมพิวเตอร์ช่วยสอนในระบบการพยาบาลสนับสนุน และให้ความรู้ต่อพฤติกรรมการดูแลตนเองของผู้ป่วยเด็กวัยเรียนโรคหัวใจพิการแต่กำเนิด - พร้อมพรรณ สัชชานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purposes of this quasi-experimental research were 1) to compare self care behaviors of school-aged children with congenital heart disease before and after receiving the computer assisted instruction in supportive educative nursing system, and 2) to compare self care behaviors of school-aged children with congenital heart disease between the group receiving the computer assisted instruction in supportive educative nursing system and the group receiving routine nursing care. Subjects were school-aged children with congenital heart disease aged between 7-12 years old who received treatment at Pediatric Cardiology Clinic, Out-Patient Department, Phramongkutklao Hospital during June to December 2011. They were assigned into the control group and the experimental group. There were 20 patients in each group. The control group received the routine nursing care. The experimental group received the computer assisted instruction in supportive educative nursing system once at the hospital. Then they were given the computer assisted instruction to review at home or at school once a week and also the researcher made a follow-up phone call for 3 consecutive weeks. Data were collected in both group after 1 month by using the self care behaviors of school-aged children with congenital heart disease questionnaire which was the reliability of .75. Data were analyzed by using mean, standard deviation, and t-test. The findings were as follows:1) The self care behaviors of school-aged children with congenital heart disease after receiving the computer assisted instruction in supportive educative nursing system was significantly improved at the .05 level. 2) The self care behaviors of school-aged children with congenital heart disease who received the computer assisted instruction in supportive educative nursing system was better than those who receiving the routine nursing care at the significant level of .05.